Rental bike services with real time chat assistance / Fikri Razi Mohd Rashid and Muhd Hafifi Supir - Mohd Rashid, Fikri Razi; Supir, Muhd Hafifi (College of Computing, Informatics, and Mathematics, 2024)
Having a rental bike service is important for visitors who decides to ride around the tourist spot such as Malacca. This system is developed because of unavailability of a rental bike system to accommodate visitors of Malacca that want to travel around the Malacca city without having to walk. The objective of this project to to design and develop a website of bike rental services with real time chat function. Then, to evaluate the chat function in the website. For webhosting configuration, Hostinger is used as a webhosting partner to deploy the website. Then, Cloudflare is used to deploy the code for chat widget, where it is integrated with Telegram bot. Methodology that will be applied within this tool such as creating vehicle rental website with user friendly interface and easy administration handling need to be created to ease tourists to rent vehicles to tour around Malacca. As a result, one of the answers to this problem is the project of bike rental website with chat widget function. The expected outcome will be the chat assistance enables users to have better user experience in terms of quality of service and fast actions, protect rental providers product from any unmentioned damages and having implementing location sending function in this project, rental providers able to respond quickly to distress calls. This all rounding methodology to create rental bike services system with real time chat widget service that can provide good user experience